Analisis Pengaruh Human Capital, Upah Minumum dan Angkatan Kerja Terhadap Pertumbuhan Ekonomi Sektor Industri di Kota Gunung Sitoli Tahun 2018-2022 - Ilman Ashari Siregar; Irma Hutagalung; Jaiton Habeahan; Juan Sibarani; Rista Lumban Gaol; Nasrullah Hidayat (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to analyze the influence of human capital, minimum wages and workforce on the economic growth of the industrial sector in Gunung Sitoli City in 2018-2022. The research method uses multiple linear regression analysis with secondary data from the Central Statistics Agency (BPS) and the Gunung Sitoli City Manpower Office. The results of the study indicate that human capital and workforce have a significant effect on the economic growth of the industrial sector, while the minimum wage does not have a significant effect. The condition of human capital in Gunung Sitoli City can be assessed based on several main indicators such as education level, workforce skills, and access to training and development of abilities. 2022 is a period in which Gunungsitoli City shows efforts to improve worker welfare through adjustments to the UMK, but still faces challenges in creating sufficient jobs to absorb the growing workforce. This study contributes to the development of local economic policies and human resource development strategies in Gunung Sitoli City.